PENDEKATAN FUNGSI SELEKSI UNTUK MASALAH PEMROGRAMAN BILEVEL FUZZY DALAM PENGOPTIMALAN RETRIBUSI JALAN TOL - , SYARIFAH INAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Optimizing toll charges problem can be described as bilevel bilinear fuzzy programming problems, namely bilevel bilinear programming problems involving the objective function coefficients having fuzzy value. The resulting problem consists of upper-level problem, which is a crisp bilinear optimization problem, implicitly determining the optimization of lower-level problem having fuzzy value. In finding the optimal solution of this problem, it can use the selection function approach under the assumption that the second-level decision makers can select a single optimal solution. In solving algorithms, this approach uses the method of ranking Yager for selecting the objective function at the lower-level problem in terms of changing fuzzy optimization on the lower-level problem into crisp optimization problems. Consequently, the optimal solution of the problem is obtained. Furthermore, applying the selection function approach on an example of a problem in optimizing toll charges.